The mask during the modern pandemic: sociological approaches and issues of interpretation - Valasaki, Maria (The Greek Review of Social Research, 2020)
The pandemic caused by the new coronavirus SARS-CoV-2, has designated an amount of issues that need investigation under modern multidimensional perspectives. One of the issues that have troubled not only -social- sciences but persons independently, is the issue of mask, which in this short article is in the center of the discussion. The use of mask is problematized in relation to the senses as Simmel (2017) approaches them, while the latter open the way for questions related to the intense social changes of the past few months. Specifically, the use of mask seems to affect not the sense of hearing itself but the way we perceive the others and ourselves through it and the way we use our bodies in relation to it; it seems that new communicational pathways are created. From the problematization of the senses it seems that medical discourse is interlaced with political discourse and it embeds in daily life designating models of power, creating in the meantime shapes such as isolation-safety, that shape the modern communicative context. Thus, under a short “kaleidoscopic” perspective, the mask is perceived as a symbol with multiple meanings, calling to attribution of interpretations and to renegotiation of concepts.